Design of a radiant panel test at reduced scale for the high throughput development of artificial turf structures. (March 2022) - Paturel, Angeline; Casetta, Mathilde; Rambour, Stijn; Janus, Ludovic; Duquesne, Sophie
Artificial turf structures are increasingly used in closed areas and have to comply with the European fire standard for building products (EN ISO 13501-1). The main test to evaluate the fire performance of flooring products is the EN ISO 9239-1 radiant panel test. The test principle is to determine the critical heat flux of floorings exposed to a forced ignition and a specific heat flux profile. As large amounts of material are needed to perform the test, the development of a radiant panel test at reduced scale was considered. The experimental design methodology was implemented to mimic the heat flux profile. The fire performance of artificial turf structures was evaluated at both scales and the results were compared. The burnt lengths of the specimens and thus the critical heat flux are similar for both scales. Thus, the downscaled device could advantageously be used for high throughput development of artificial turf structures.